The effects of oxcarbazepine, levetiracetam, and lamotrigine on semen quality, sexual function, and sex hormones in male adults with epilepsy. (11th June 2018) - Wu, Dongmei; Chen, Lang; Ji, Fayuan; Si, Yang; Sun, Hongbin
Summary: Objective: To investigate the effects of antiepileptic drugs (AEDs; oxcarbazepine [OXC], levetiracetam [LEV], and lamotrigine [LTG]) on semen quality, sexual function, and sex hormones in male adults with epilepsy. Methods: Individual treatment with OXC, LEV, or LTG was randomly assigned to 38 newly diagnosed male adult patients with epilepsy. Semen quality and sex hormones were measured before treatment and 6 months after taking the medicine. A questionnaire was administered using the International Index of Erectile Function Scale‐5 and the Premature Ejaculation Diagnostic Tool Self‐Assessment Scale to evaluate sexual function, followed by an analysis of the comparison between the treated patients and healthy volunteers (healthy controls) as well as the changes and differences between the patients themselves before and after treatment. Results: The total sperm count, fast forward movement rate (FFMR), survival rate, and normal sperm rate in the group with epilepsy were lower than those in healthy controls ( P < .05). The FFMR and survival rate of sperm after OXC treatment were significantly higher than before treatment ( P < .05). All semen parameters after LEV and LTG showed a possible trend for improvement, but no significant statistical difference. There was no significant difference in sexual function between patients and the control group, as well as before and after treatment with the 3 different AEDs. There was no significant difference in sex hormone levels in the epilepsy group before treatment compared with the healthy controls, or when compared after treatment with the 3 different AEDs. The marital rate and fertility rate of patients with epilepsy were significantly lower than those of healthy controls ( P < .05). Significance: The semen quality of males with epilepsy is decreased even before treatment. The AEDs (OXC, LEV, and LTG) have no significant effect on sexual function and sex hormones, and OXC can improve the sperm FFMR and survival rate.